ANALYSIS OF THE CONTRIBUTION OF ENTREPRENEURSHIP ACCOUNTING TO THE SUCCESS OF MICRO AND SMALL BUSINESSES (REMUNOM, 2025)
This article aims to address the importance of entrepreneurial accounting as a direct influence on the success of micro and small businesses. The lack of support from accounting tools and the work of an accountant leads to various disadvantages, such as tax and legal problems, lack of financial control, and compromised company health. Therefore, the guiding question of this research is: How does entrepreneurial accounting contribute to the success of micro and small businesses? The general objective is to analyze how entrepreneurial accounting can contribute to the success of micro and small businesses. The specific objectives are to describe the concepts of accounting and entrepreneurship, demonstrate the importance of entrepreneurial accounting for the success of micro and small businesses, demonstrate that accounting enables more effective decision-making, and present essential accounting tools for business expansion. This research uses a qualitative approach. Explanatory, exploratory, and bibliographic research were used. The study demonstrates the importance of accounting for the success of micro and small businesses, making it essential for exploring the topic. Besides expanding and integrating knowledge, it can demonstrate that accounting is more than just the study of entities. It demonstrates that entrepreneurial accounting in micro and small businesses is an indispensable element for effective management.